Dynamic stability of hydraulic gates and engineering for flood prevention - Ishii, Noriaki 1946-; Anami, Keiko 1974-; Knisely, Charles W. (Advances in civil and industrial engineering (ACIE) book series, 2018)
This book explores dynamic stability of hydraulic gates and engineering for flood prevention. It covers the history of gate failures and overview of vibration mechanisms, explores vibrations within resonator and stability concepts, the basic concepts of gate discharge and flow stability, and streamwise gate vibration